Implementasi Pendidikan Agama Islam dan Budi Pekerti dalam Meningkatkan Sikap Toleransi dan Prestasi Belajar Siswa Sekolah Dasar Swasta di Kota Batam - Ikhwanuddin, Ikhwanuddin; Sumianti, Sumianti; Miswanto, Miswanto (Riviera Publishing, 2026)
This study aims to examine the implementation of Islamic Religious Education and Character Education in improving tolerance attitudes and learning achievement of private elementary school students in Batam City. Batam City, as a multicultural area with diverse ethnicities, cultures, and religions, requires an educational approach capable of instilling tolerance values from an early age. This research employs a qualitative approach using a case study method conducted in three private elementary schools: SDS Al Furqan Sekupang, SDS Islam Nurul Haq Batu Aji, and SDS An-Nahdah Sekupang. Data collection was carried out through classroom observation, in-depth interviews with Islamic education teachers and grade IV-V students, and documentation of learning activities. Data analysis techniques used the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of Islamic education that integrates religious moderation values, teacher exemplary behavior, and contextual approaches can foster mutual respect, cooperation, and empathy among students. The improvement in tolerance attitudes impacts the creation of a conducive and harmonious learning climate, which supports enhanced student learning achievement. Supporting factors include teacher competence, school policy support, and a positive learning environment, while inhibiting factors encompass limited learning time and variations in student backgrounds. This research confirms that Islamic Religious Education not only plays a role in character formation but also contributes significantly to improving learning quality in multicultural environments.